2014
DOI: 10.1063/1.4884275
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of exciton-polaron transition in molecular assemblies: The variational approach

Abstract: Dynamics of excitonic polaron formation in molecular systems coupled to an overdamped bath are investigated using the Dirac-Frenkel variational principle and Davydov D1 Ansatz. Using a two-site model system we show that a few qualitatively distinct relaxation regimes of an optically created exciton are possible, depending on the timescale of bath fluctuations. A slow bath always leads to adiabatic polaron formation. Non-adiabatic exciton self-trapping occurs when the system is strongly coupled to a fast bath. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…The current paradigm is that after photoexcitation the excitonic states are established, possibly with accompanying polaron formation. 57 The excitons then diffuse by a classical random walk through the polymer. 5 While separately the diffusive transport and wavelike motion have been described, how the former emerges from the latter is a subject under debate, 56 typically ignored when discussing the exciton migration.…”
Section: Introductionmentioning
confidence: 99%
“…The current paradigm is that after photoexcitation the excitonic states are established, possibly with accompanying polaron formation. 57 The excitons then diffuse by a classical random walk through the polymer. 5 While separately the diffusive transport and wavelike motion have been described, how the former emerges from the latter is a subject under debate, 56 typically ignored when discussing the exciton migration.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis performed here shows that the interaction electron-phonon coupling results in the formation of large polarons, and these are responsible for high-frequency conductivity in magnetite. Chorošajev et al (2014) studied the dynamics of the formation of polaron excitons in molecular systems coupled to an overamplified bath using the Dirac-Frenkel variational principle and the Davydov Ansatz D1. They showed that the timescale of the polaron formation can be defined by the timescale of resonant coupling quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining dynamics of open quantum systems, i.e., quantum systems that are identified as separate from its environment, yet remain in thermal contact with it, is one of the most general quantum mechanical problems. Its applicability range from excited state relaxation in optical response [1,2], energy transport in molecular aggregates [3][4][5][6][7][8], photosynthetic complexes [9][10][11][12] and others [13][14][15][16][17]. Prevalent theoretical description is given in terms of system-bath model in constant temperature bath conditions [18,19], where the system degrees of freedom are coupled to the bath-induced thermal fluctuations representing the environment, e.g., phonons or vibrational motion of surrounding molecules.…”
Section: Introductionmentioning
confidence: 99%